2021
DOI: 10.3390/ijerph18158015
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Aflatoxins in Edible Vegetable Seeds and Oil Samples Available in Pakistani Retail Markets and Estimation of Dietary Intake in Consumers

Abstract: Aflatoxins (AFs) are secondary metabolites toxic to humans as well as animals. The environmental conditions, conventional agricultural practices, and illiteracy are the main factors which favor the production of AFs in food and feed. In the current study 744 samples of vegetable seeds and oils (soybean, sunflower, canola, olive, corn, and mustard) were collected and tested for the presence of aflatoxin B1 (AFB1) and total AFs. Liquid-liquid extraction was employed for the extraction of AFs from seeds and oil s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…AFs and ZEA were found in sunflower oils in China and Tanzania [11,24]. In Pakistan, AFB1 contamination was found in soybean, corn, sunflower, and olive oils from imported and local samples [25].…”
Section: Occurrence Of Multiple Mycotoxins In Edible Vegetable Oilsmentioning
confidence: 96%
“…AFs and ZEA were found in sunflower oils in China and Tanzania [11,24]. In Pakistan, AFB1 contamination was found in soybean, corn, sunflower, and olive oils from imported and local samples [25].…”
Section: Occurrence Of Multiple Mycotoxins In Edible Vegetable Oilsmentioning
confidence: 96%
“…Edible plant oils like maize oil, olive oil, peanut oil, sunflower oil, and coconut oil are highly abundant and popular globally, as they are an important dietary source of everyday nutrition. Inappropriate practices in different stages of edible plant oil production such as packaging, transportation, and storage, could encourage mold growth resulting in mycotoxin contaminations in oils (Waqas et al, 2021). In addition, owing to the novel industrial processes, agricultural practices, climatic changes, and environmental pollution, new toxic residues in oil have been increasing (Farré and Barceló, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxins, the culprit of mycotoxicosis, are widely distributed in various feed materials and products, which seriously harm human and animal health. Humans have a wide range of opportunities to ingest mycotoxins and develop related diseases. , Deoxynivalenol (DON) is one of the most common mycotoxins. Studies have shown that 96.4% of feed samples were contaminated with DON in China, and DON-derivative deoxynivalenol-3-glucoside was detected in 94% of wheat samples in Argentina. , DON and its derivatives were also determined in human food. , DON has been extensively studied for its toxicity and mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Humans have a wide range of opportunities to ingest mycotoxins and develop related diseases. 1,2 Deoxynivalenol (DON) is one of the most common mycotoxins. Studies have shown that 96.4% of feed samples were contaminated with DON in China, and DONderivative deoxynivalenol-3-glucoside was detected in 94% of wheat samples in Argentina.…”
Section: Introductionmentioning
confidence: 99%